INNOVATIVE PEDAGOGICAL POTENTIAL OF INTEGRATING LITERATURE INTO HISTORY TEACHING - Akbutayeva Nafisa Bozarovna,; Ahmedshina Faniya Abzalovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: The article explores the pedagogical significance of using fiction in the process of teaching history in schools. Research indicates that fiction plays a vital role not only in the dissemination of historical knowledge but also in the formation of students' national and moral values. The article analyzes the methodological aspects of utilizing literary texts and demonstrates their effectiveness within the educational process.